Higher constitutive IL15Rα expression and lower IL-15 response threshold in coeliac disease patients - David Bernardo; José Antonio Garrote; Y Allegretti; Alberto J. León; Ernesto A. Gómez; Jesús F. Bermejo-Martín; Carmen Calvo; Sabino Riestra; Luis Fernández‐Salazar; Alfredo Blanco-Quirós; Fernando G. Chirdo; Eduardo Arranz (2008)
Summary The IL-15 triggering effect of gliadin is not exclusive to coeliac disease (CD) patients, whereas the secondary response is CD specific. We have studied the expression of the IL-15 receptor, and the IL-15 response upon stimulation, in non-CD and CD patients, and the possible existence of a lower immunological threshold in the latter. Forty-two CD patients (20 on a gluten-containing diet, GCD, and 22 on gluten-free diet, GFD) and 24 non-CD healthy individuals were studied. IL15Rα mRNA expression, and tissue characterization, were assayed in the duodenum. Biopsies from six CD patients on GFD and 10 non-CD individuals were studied in vitro using organ culture in basal conditions, as well as after IL-15 stimulation discarding basal IL-15 production. Secretion of immune mediators was measured in the culture supernatants. IL15Rα mRNA expression was increased in CD patients, as compared with non-CD controls (on GFD P = 0·0334, on GCD P = 0·0062, respectively), and confirmed also by immunofluorescence. No differences were found between CD patients on GFD and on GCD. After in vitro IL-15 stimulation, IL15Rα expression was only triggered in non-CD controls (P = 0·0313), though it remained increased in CD patients. Moreover, IL-15 induced a more intense immunological response in CD patients after triggering the production of both nitrites and IFNγ (P = 0·0313, P = 0·0313, respectively). Gliadin-induced IL15 has a lower response threshold in CD patients, leading to the production of other immune mediators and the development of the intestinal lesion, and thus magnifying its effects within the CD intestine.